Recent Advances in Lectin-Based Affinity Sorbents for Protein Glycosylation Studies - Goumenou, Anastasia; Delaunay, Nathalie; Pichon, Valérie (Frontiers in Molecular Biosciences, 2021)
Glycosylation is one of the most significant post-translational modifications occurring to proteins, since it affects some of their basic properties, such as their half-life or biological activity. The developments in analytical methodologies has greatly contributed to a more comprehensive understanding of the quantitative and qualitative characteristics of the glycosylation state of proteins. Despite those advances, the difficulty of a full characterization of glycosylation still remains, mainly due to the complexity of the glycoprotein and/or glycopeptide mixture especially when they are present in complex biological samples. For this reason, various techniques that allow a prior selective enrichment of exclusively glycosylated proteins or glycopeptides have been developed in the past and are coupled either on- or off- line with separation and detection methods. One of the most commonly implemented enrichment methods includes the use of lectin proteins immobilized on various solid supports. Lectins are a group of different, naturally occurring proteins that share a common characteristic, which concerns their affinity for specific sugar moieties of glycoproteins. This review presents the different formats and conditions for the use of lectins in affinity chromatography and in solid phase extraction, including their use in dispersive mode, along with the recent progress made on either commercial or home-made lectin-based affinity sorbents, which can lead to a fast and automated glycosylation analysis.